The relationship between students’ concentration level and smash result competency in badminton extracurricular - Zamahsyari Syayyif Al Fathi; Setyo Hartoto; Bayu Budi Prakoso (Sriwijaya Journal of Sport, 2022)
This correlation study aims to determine the relationship between the concentration of badminton extracurricular students on smash accuracy. The study population was all extracurricular students at SMPN 5 Pamekasan and SMP Plus Nurul Hikmah as many as 94 students (M: 60; F: 34). Sampling using simple random sampling resulted in 56 students (M: 28; F: 28). Concentration was measured using the Concentration Grid Test (validity t=8.771, p<0.05) and smash accuracy was measured using the Smash Ability Test (validity, r= 0.926 and reliability, test-retest= 0.9). The results show that the average value of concentration is 8.07 (less concentration) and the average value of smash accuracy is 48.86 (medium smash). The normality test showed that the concentration distribution was not normal (p= 0.0006<0.05) and the smash accuracy was normal (p= 0.2>0.05). Spearman's rho correlation showed that there was no relationship between concentration and smash accuracy (r= 0.146, p= 0.284>0.05). There is no relationship because the students' smash ability is still lacking and when they do it too fast the concentration that should be able to be maximized properly becomes less good or less than optimal. It can be concluded that research on the relationship between students' concentration levels and badminton extracurricular smash skills has no relationship.